Development of salted egg powder by the addition of garlic extract - Herly Evanuarini; Agus Susilo (Universitas Sebelas Maret, 2022)
Objective: The objective of this study was to determine the use of garlic extract in salted egg powder based on the physicochemical quality, to improve nutrition, shelf life and consumer preference.Methods: This study used was a laboratory experimental design with a completely randomized design with 4 treatments and 4 replications. The treatment were without the addition of garlic extract as a control (P0), 5% (P1), 10% (P2), and 15% (P3) addition of garlic extract to salted egg powder. Pan drying method at 60°C for 6 hours was used as a drying method. The variables measured were yield, Lightness, redness, and blueness color, moisture content, antioxidant activity. Analysis of Variance (ANOVA) was used as data analysis, if there was a significantly different effect, it was continued with Duncan's Multiple Range Test (DMRT).Results: This study produced salted egg powder with a yield of 27.22-36.77%, color L of 75.35-80.33, color a* 5.01-6.33, color b* 26.99-31.66, moisture content of 2.23-2.77%, and antioxidant activity of 2.30-11.64%.Conclusions: The best treatment of this research is salted egg powder with the addition of garlic extract as much as 15% and produces a product with a yield of 36.77%, color L of 75.35, color a* of 6.33, color b* of 31.66, moisture content of 2.77 and antioxidant activity of 11.64%.